Factors considered by prospective students in choosing major of online business and marketing - Hadiyanti, Utami; Suroso, Agus; Setyanto, Refius Pradiptya (Jurnal Akuntansi, Manajemen dan Ekonomi, 2018)
The purpose of this study is to analyze the factors that become the consideration of prospective students in the decision to choose the major of online business and marketing. The type of research used is exploratory. This study used a sample of 76 prospective students. Data analysis used factor analysis. Results of the analysis show that the factor considered by the prospective students in choosing the major of online business and marketing is the student’s perception factor. While, the factors considered by prospective students who do not choose the major of online business and marketing is due to perception factors that include family perception and perception of friends. The conclusion of this study is that the student perception becomes factor considered by the prospective students in choosing and not choosing the major of online business and marketing at Public Vocational High School 1 Banyumas.